Potential bioactive compounds found in three different Insect species (Periplaneta americana, Chrysomya megacephala, Oxya serville): Steroids and protein content - Hendri, Afrizal; Diansyah, Sufal; Meulisa, Ade Irma; Nurdin, Muhammad (Universitas Malikussaleh, 2024)
Cockroaches, houseflies and green locusts are three types of insects that are available around us, and even their presence tends to be a carrier of disease (host) and pests in agriculture. Based on these conditions, it is necessary to conduct an initial study of the potential bioactive compounds contained in the three types of insects, especially steroid and protein content as candidates for ˜ecdysteroids for crab moulting stimulants, as well as their social and economic potential. This research is qualitative with the following stages: i) insect collection using traps, ii) insect extraction, iii) chemical compound testing of insect extracts, and iv) proximate testing. The results showed that the insect animals tested were cockroaches, flies, and adult grasshoppers, and they were positive for steroid compounds tested using the Liebermann-Burchard method. From the results of the proximate test, the three insect animals have crude protein (%) 32.5 for cockroaches, 33.5 for flies, and 30.5 for grasshoppers. From a social perspective, utilising these animals will reduce disease-carrying hosts in the community. Economically, it will impact the emergence of a business chain in the supplier segment.Keywords: Aquaculture; Insects; Moulting; Protein; Steroid